Correlation Between Chlamydia trachomatis Infections and Interferon Gamma (IFN-γ) inWomen With spontaneous abortion - Salman H. Amal; Hana B. Dalya; Salman L. Shaymma (College of Pharmacy / Mustansiriyah University, 2008)
The objective of this study was to find out the correlation between Chlamydia trachomatis infection and production of Interferon gamma (IFN- γ) with respect to abortion in women that had spontaneous abortion. Serum was collected from the women that had abortion and woman with successful pregnancy, and all samples were analysed for IgM specific antibodies for Chlamydia trachomatis and IFN- γ by commercially available Enzyme- Linked Immunosorbent Assay (ELISA) kits. A highly significant difference in the serum level of IgM specific antibodies of Chlamydia trachomatis and IFN- γ was found in women that had abortion compared with successful pregnancy (P<0.001), and a highly significant positive correlation between them (r=0.503, p<0.001) in sera of women that had abortion. The data of this study strengthen the possibility that IFN-γ may explain the role of type 1 cytokines in the pathogenicity of abortion in the positive group for Chlamydia trachomatis.